Constructing the Desirable Reader in Swedish Contemporary: Literature Policy - Lindsköld, L.; Hedemark, Å.; Lundh, Anna (2020)
This study contributes to a growing number of critical studies of reading that are seeking to understand how reading is constructed socially and politically. It addresses issues concerning why certain types of reading are deemed more appropriate than others in various contexts and historical eras. The aim of the study is to explore constructions of reading, reading promotion, and readers that can be identified in Swedish literature policy 2012-2013 in order to make explicit the implicit assumptions embedded in the politics of readinğ This is achieved through a discourse analysis of the Swedish Government Commission report on Literature from 2012 and the subsequent Government Bill from 2013. The analysis focuses on the construction of the 'problem' that reading is supposed to solve, the subject-position of the reader, and the knowledge practices that underpin the construction of the 'problem'. The analysis reveals that the main 'problem' is the changing reading habits of the Swedish population and the decline in the reading ability of Swedish children and youth. This is seen as a threat to several important societal values, such as children's learning and development, democracy, “the culture of reading”, Sweden's economic competitiveness, and the market for literature. Responsibility for the problem is placed on the school system, parents, and the use of computers and the Internet. The remedy is seen as the promotion of the right kind of literature. Furthermore, the analysis illustrates how the subject position of the appropriate reader is formed around the notion of the harmful non-reader. Similar dividing practices are constructed around youth/adult, pupil/teacher, child/parent, and son/father where the latter is expected to make the former a reader and thereby a desirable subject. The analysis also shows how two contradictory knowledge practices are joined together in the policy texts, where seemingly rational, objective, and empirical research is paired with humanistic Bildung values.